Z-WASTE: APLIKASI RAMAH LINGKUNGAN BERBASIS MOBILE - I Gede Wiryawan; Maulida Dwi Agustiningsih; Muhammad Yusuf; Vyan Ary Pratama; Linda Dwi Wahyuningsih (LPPM STMIK STIKOM Indonesia, 2021)
Plastic waste has reached pandemic levels worldwide. It adversely affects wildlife, wildlife habitat, and humans. Meanwhile, adopting information technology may reduce plastic waste problem. In this study, a Zerowaster application was developed that can provide green spot information. The idea of the developed application is unique from existing applications. Zerowaster application does not make plastic waste as an object that is informed, but rather shows information on clean places or where there is no trash. Prototype method is used in this study. And Blackblox is chosen as a method to test the application. Application development is started by desgining interface, then developinng a webpage admin, implementing Application Programming Interface (API) and Geographic Information System (GIS). The result shows that Zerowaster application running well on mobile application as well as showing green spot for the users.